Nutrient removal by Persian lemon harvest in Nayarit and Veracruz, Mexico - Mellado Vázquez, Adriana; Salazar García, Samuel; Álvarez-Bravo, Arturo; Hernández-Guerra, Carlos (Revista Mexicana de Ciencias Agrícolas, 2017)
The amount of nutrients removed by the harvest of Persian lemon is unknown, a fact that can contribute to the better management of nutrition. The objective was to know the removal of nutrients by the Persian lemon crop in flowering flows of spring and winter 2013 in Nayarit, in orchards temporary and irrigation, and in Veracruz flowering flowering summer and winter 2015, in two Temporary orchards. In each orchard five trees were chosen and buds were marked spring, summer and winter, By tree six fruits were harvested at physiological maturity and in the dry matter was determined the concentration of N, P, K, Ca, Mg, S, Fe, Cu, Mn, Zn, B. In Nayarit, the irrigation favored the removal of N and Zn and the interaction water * flow of flowering affected the removal of Ca. The orchards of Nayarit should be fertilized with greater amount of S in spring and with more P, Mn and B in the winter. To improve the nutrition of Persian lemon in Veracruz, the application of P, Ca, Fe and Cu after the harvest from summer sprouting should be included, as well as the application of N, Ca, Zn and B after the harvest of winter sprouting.